المرابحة بين التطبيقات الفعلية في المؤسسات المالية الإسلامية والإشكالات القانونية في محاكم الدولة، والحاجة الى التقنين؛ نموذج الإمارات العربية المتحدة - فضل رحيم عبد الرحيم
Islamic financial institutions face significant challenges in courts in the country when they file cases against customers who have failed to meet their Murabahah-based financial obligations. Courts operating in UAE look at these cases in the same way as cases filed by conventional banks. The courts use the prevailing laws to recover the rights of Islamic financial institutions in absence of laws related to Murabaha in the banking sector. In some cases, the court appoints ‘Islamic banking expert’ who submits his report to the court in light of which the court decide to return the rights of the Islamic financial institution from the customer depending on the applicable laws. It is worth mentioning that the Islamic banking expert who submits his report to the court, does not have an authenticated legally approved source of law from which he derives the provisions of Islamic banking for presenting his opinion before the court and usually depends on his banking experience and most of the time do mistakes. Therefore, the Islamic banking industry in UAE needs Banking Murabahah Act. The meaning of “Enacting Banking Murabahah” in this research is the need of drafting new Shari’ah compliant law / act arranged and codified in form of modern laws to be an easy and specific reference for the judges, lawyers and the Islamic financial institution’s practitioners. This purpose could be served by introducing articles related to Murabahah in the banking sector in Federal Commercial Transactions Law. The aim of this study, is to prove the necessity of enacting of Murabaha in the banking sector on the basis of Shari’ah rules and principles, in order to comply the legal judgment with the Shari’ah principles of the contracts. In this way, Islamic banks will follow a unified approach to understand the legal and Shari’ah provisions of the Banking Murabaha. This will eliminate the factor of financial and spiritual loss from which the Islamic financial industry is suffering in absence of laws related to the Murabahah in the banking sector. To identify the need of the Islamic financial industry for the enacting of the Murabahah in the banking sector, the researcher intended to follow the qualitative approach in his research and conducted personal interviews to collect data and information with scholars, university professors, lawyers, experts, accountants, auditors, reviewers, Islamic bankers and practioners. The result of the research is that the Islamic Financial Institutions are in need of new legal act for Murabahah for the smooth running of the functions of Islamic banking operations from Shari’ah and Legal perspective.